2004
DOI: 10.1080/08037050410016465
|View full text |Cite
|
Sign up to set email alerts
|

The effect of clothes on sphygmomanometric and oscillometric blood pressure measurement

Abstract: This study shows that measuring blood pressure with the manometer's cuff over the subject's sleeve does not differ significantly from non-sleeved arm measurements. This is true for a sample that includes normotensive as well as hypertensive persons with a wide age range. For clinical practice, the not significant mean differences of 0.5-1.1 mmHg are interpreted as not relevant. In this study with a statistical power to find a difference of 4 mmHg, blood pressure measurements were found to be equivalent with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
33
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 3 publications
6
33
0
3
Order By: Relevance
“…However, this difference was neither clinically important nor statistically significant. Our results confirm the findings of the 3 previous studies [3][4][5] and show that, regardless of method, assessment of blood pressure over a bare arm and over a sleeved arm both yield accurate results. A comparison of the methodologies of all 4 studies is shown in Table 4.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, this difference was neither clinically important nor statistically significant. Our results confirm the findings of the 3 previous studies [3][4][5] and show that, regardless of method, assessment of blood pressure over a bare arm and over a sleeved arm both yield accurate results. A comparison of the methodologies of all 4 studies is shown in Table 4.…”
Section: Discussionsupporting
confidence: 82%
“…Although they found no significant difference in the effect of clothing on blood pressure readings, the study was limited by their design of measuring blood pressure below a rolled-up sleeve. The third study, conducted by Liebl et al, 5 was published while our study was in progress. Their study, which involved 201 patients, compared blood pressure measurements taken over a sleeved arm and a bare arm with both sphygmomanometric and oscillometric devices.…”
mentioning
confidence: 99%
“…The authors found that readings taken over the sleeve of a shirt, blouse or light sweater were not statistically different from those taken on bare arms. These results appear to agree in magnitude and direction with findings from 3 previous studies [4][5][6] that investigated the accuracy of blood pressure measurement over clothing.…”
supporting
confidence: 82%
“…In clinical practice, these recommendations on removal of clothing are often not followed, and for practical or comfort reasons, clothing is left underneath the cuff. There are some studies that support this practice [1,[5][6][7][8][9], but these have some flaws. Previous studies had the limitations of very few BP readings, use of only one standard cuff bladder size, and absence of randomization.…”
Section: Introductionmentioning
confidence: 97%
“…As BP varies depending on conditions such as body position and stress, standardization of BP measurement is mandatory. Several guidelines are available with advice on measurement device, position of body and arm during BP measurement, speed of bladder inflation and deflation, and rest interval before taking a measurement [1][2][3][4]. Some of these guidelines explicitly recommend placement of the cuff around the bare arm (BA) of the patient or state that automatic wrist monitors are the only devices for which there is no need to remove clothing [2].…”
Section: Introductionmentioning
confidence: 99%